Landscape and Climate Specifics for Water Sensitive Urban Design in Vladivostok. Issue 4 (February 2020) - Kazantsev, P; Marus, Y; Smelovskaya, A
Abstract: The article concerns with the conditions and special aspects of urbanized areas' natural hydrological cycle recovery in monsoon climate and hummocky topography conditions of Southern Primorye through the example of Vladivostok. Natural infrastructure and catchment area original state and anthropogenic transformation in urbanization process of Murav'ev-Amursky peninsula Southern part is analyzed. Through the natural landscapes estimation three types of catchment areas due to seasonal changing of their contribution to river system water content were defined. Their correlating with the transport infrastructure and industrial areas locations made it possible to find out problematic areas and water system restoration reserves.